1994
DOI: 10.1021/bi00249a034
|View full text |Cite
|
Sign up to set email alerts
|

nifU Gene Product from Azotobacter vinelandii Is a Homodimer That Contains Two Identical [2Fe-2S] Clusters

Abstract: The nifU gene product is required for the full activation of the metalloenzyme nitrogenase, the catalytic component of biological nitrogen fixation. In the present work, a hybrid plasmid that contains the Azotobacter vinelandii nifU gene was constructed and used to hyperexpress the NIFU protein in Escherichia coli. Recombinant NIFU was purified to homogeneity and was found to be a homodimer of 33-kDa subunits with approximately two Fe atoms per subunit. The combination of UV/visible absorption, variable-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
141
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 51 publications
3
141
0
1
Order By: Relevance
“…This strain is not further impaired in diazotrophic growth, so it seems unlikely that Nif IscA significantly contributes to nitrogenase maturation under the conditions used in the present work. 1 Another possibility is that, as previously suggested, the isc-encoded system could make some very minor contributions to nitrogenase maturation, but this possibility has not been tested because deletion of the A. vinelandii isc operon is lethal (5). Yet another possibility is that an A. vinelandii gene, which we designate nfuA, that encodes a product bearing primary sequence homology to the C-terminal domain of NifU could contribute to nitrogenase-specific Fe-S cluster biogenesis in the absence of intact NifU function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strain is not further impaired in diazotrophic growth, so it seems unlikely that Nif IscA significantly contributes to nitrogenase maturation under the conditions used in the present work. 1 Another possibility is that, as previously suggested, the isc-encoded system could make some very minor contributions to nitrogenase maturation, but this possibility has not been tested because deletion of the A. vinelandii isc operon is lethal (5). Yet another possibility is that an A. vinelandii gene, which we designate nfuA, that encodes a product bearing primary sequence homology to the C-terminal domain of NifU could contribute to nitrogenase-specific Fe-S cluster biogenesis in the absence of intact NifU function.…”
Section: Discussionmentioning
confidence: 99%
“…The Azotobacter vinelandii NifU protein is an ϳ60-kDa homodimer proposed to provide a molecular scaffold for formation of [Fe-S] clusters or Fe-S cluster precursors required for full activation of the nitrogenase catalytic components (1,2). Primary sequence comparisons among NifU homologs indicate that it is a modular protein having three distinct domains (3,4).…”
mentioning
confidence: 99%
“…Effect of the V102E Substitution on IscU Interactions with Hsc66 and Hsc20 -In addition to IscU, diazotrophpic organisms contain a second iron-sulfur template protein, NifU, that functions in the assembly of the nitrogenase protein (28,29). The N-terminal regions of NifU proteins display sequence homology to IscU proteins, but there are no known chaperones associated with iron-sulfur cluster assembly specific to the nitrogen fixation machinery (5,12).…”
Section: Stimulation Of Hsc66mentioning
confidence: 99%
“…Enzymes involved in Fe-S cluster assembly were first identified in the nif (nitrogen fixation) operon in Azotobacter vinelandii (2). Genetic and biochemical studies have shown that two gene products, NifS and NifU, are essential for assembly of the Fe-S clusters in nitrogenase (3)(4)(5)(6). Subsequent studies in a wide variety of prokaryotes resulted in the identification of the isc (iron-sulfur cluster assembly) operon (7,8), which encodes the translational regulator IscR (9), cysteine desulfurase IscS (7), scaffold proteins IscU (10) and IscA (11,12), chaperone proteins HscA and HscB (13), and ferredoxin Fdx.…”
mentioning
confidence: 99%